Teaching Writing by Using Glogster Application - Vita Vendityaningtyas; Erisya Kusuma Wardhani (English Teaching Journal : A Journal of English Literature, Language and Education, 2021)
Writing tasks seemingly becomes high prerequisite for students in university or college. The importance of feedback and learning media is the main thing. This article is aimed at: 1) finding the use of Glogster application in writing; 2) finding the strength of Glogster application in writing; and 3) finding the challenge of Glogster application in writing. Classroom observation research is used as the method in this article, which straightly observe teaching process, takes notes, and/or codes instructional performances in the classroom. Glogster is a helpful platform for presentation and interactive learning since it combines text, pictures, videos, music in one place. This application works in some steps where firstly the user has to register on the website to create the glogster account. Then, he can choose countless templates, as he desires. The template can be freely edited and attached by pictures or videos. The users can also share this glog with friends or teacher to get the comment/feedback. As positive outcome, this application motivates the students to even re-write his task due to unintentionally deletion. Most of the experimented students revealed positive insights of Glogster and supportive learning distinguished instruction learning experience. The combination of multimedia and web tools offers flexibility in learning and improves the reading skills, the learning strategies, internet search words, as well as comments comprehension. On the other hand, user only can use freely for 7 days and has to pay to get the premium feature for prolonged use. The students definitely should provide themselves with the devices such as computers or laptop. The stabilized internet connection surely plays important role. These needs are vital to concern in reaching the best result of teaching and learning activities as well as facing the digital era of technology.